(untitled) (Journal of Telenursing (JOTING), 2024)
This research aims to determine the factors that influence the incidence of stunting in toddlers in East Kotawaringin Regency, Central Kalimantan. The method used is a quantitative analytical survey with a cross-sectional study approach, and the data analysis used is the chi-square test. The research results show a relationship between family knowledge and the incidence of stunting with a value of p = 0.008. There is a relationship between exclusive breastfeeding and the incidence of stunting with a value of p = 0.005. There is a relationship between the birth weight of the baby and the incidence of stunting with a value of p = 0.000. There is a relationship between a history of diarrhea and the incidence of stunting with a p-value = 0.000. In conclusion, there is a relationship between family knowledge, exclusive breastfeeding, birth weight, and history of diarrheal disease and the incidence of stunting. Keywords: Exclusive Breastfeeding, Birth Weight, Family Knowledge, History of Diarrhea, Stunting